Technology, temporality, and the study of Central Asia: an introduction - Van Der Straeten, Jonas; Obertreis, Julia (Central Asian Survey, 2022)
This issue is dedicated to the question of how research on technology and its inherent temporality and materiality can enhance our understanding of geography, culture and history in Central Asia. The articles provide fresh ideas on Central Asia as a region by unpacking the "hard" infrastructural base of its cultural, social, and economic geography. They offer a more inclusive view on Central Asian landscapes, focusing on permanent material structures and vernacular practices that are often overlooked in conventional historiography and social studies research. Finally, they explore how research on technology both supports and challenges the primacy of political history in defining the historical periods and legacies of Central Asia. The papers cover about 150 years of history, with case studies on what are today Kazakhstan, Uzbekistan, Tajikistan, and Mongolia. This introductory essay summarizes their key insights, situating them in a wider debate on technology in and beyond Central Asia.
CRIS-Team WoS Importer:2022-06-24
Keywords: technology; infrastructure; temporality; post-Soviet; history